Molecular cytotaxonomy of the Triatoma brasiliensis species subcomplex (Hemiptera, Triatominae) - Alevi, Kaio Cesar Chaboli [UNESP]; Bittinelli, Isadora de Freitas [UNESP]; Delgado, Luiza Maria Grzyb [UNESP]; Madeira, Fernanda Fernandez [UNESP]; de Oliveira, Jader [UNESP]; Lilioso, Maurício; Folly-Ramos, Elaine; da Rosa, João Aristeu [UNESP]; Azeredo-Oliveira, Maria Tercília Vilela [UNESP] (Elsevier, 2020)
The Triatoma genus is paraphyletic, and its species are grouped into complexes and subcomplexes. Given the fact that species that make up a given subcomplex generally share chromosomal traits, we analyzed the distribution of AT- and CG-rich DNA of the T. brasiliensis species subcomplex, in order to establish affinities among members of the T. brasiliensis subcomplex based on chromatin and chromosome traits and develop an identification key for the four monophyletic Triatoma subcomplexes from South America. All species exhibited a CG-rich X sex chromosome and autosomes, as well as an AT-rich Y sex chromosome. This feature can be used as a diagnostic characteristic to determine whether a given species is a member of the T. brasiliensis subcomplex, because it enables the differentiation of these species from all Triatoma of South America. Thus, we confirmed the chromosomal relationship of the T. brasiliensis species subcomplex and developed a dichotomous key based on the chromocenter to differentiate the species from this subcomplex from the other monophyletic Triatoma subcomplexes from South America.
Keywords: Chagas disease vectors; CMA3/DAPI fluorochromes; Cytogenetics; Taxonomy; Triatominae